1996
DOI: 10.1243/pime_proc_1996_210_479_02
|View full text |Cite
|
Sign up to set email alerts
|

Expressions for the Viscosity of Liquid/Vapour Mixtures: Predicted and Measured Pressure Distributions in a Hydrostatic Bearing

Abstract: The present paper reports the correlation between the predicted performance and experimental data obtained from a hydrostatic thrust bearing under conditions designed to produce phase change due to viscous dissipation within the lubricant. The predicted values of pressure distribution indicate that the best correlation is obtained when the viscosity of a two-phase mixture is assumed to be the volume average of the viscosity of the individual phases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…The gas density is given by the ideal gas law and thus varies with pressure and temperature whereas the liquid density is constant. The viscosity is determined using 18 …”
Section: Numerical Modelmentioning
confidence: 99%
“…The gas density is given by the ideal gas law and thus varies with pressure and temperature whereas the liquid density is constant. The viscosity is determined using 18 …”
Section: Numerical Modelmentioning
confidence: 99%
“…Saadat and Flint [23] compared predictions and measurements of pressure in a two-phase flow thrust bearing and found that the best formula is:…”
Section: Fluid Propertiesmentioning
confidence: 99%
“…Σε αυτή τη σχέση όταν το ιξώδες απειρίζεται ο τελευταίος όρος γίνεται μηδέν, έτσι δεν αντιμετωπίζεται πρόβλημα όταν στο μίγμα υπάρχει στερεή φάση. Σύμφωνα με τους (Saadat & Flint, 1996) αυτή η σχέση δίνει τιμές για το ιξώδες σε καλή συμφωνία με τις πραγματικές τιμές σε μίγμα υγρό-αέριο και μάλιστα οι τιμές είναι σε καλύτερη συμφωνία σε σχέση με τις αντίστοιχες που δίνει η σχέση (5.33).…”
Section: φυσικές ιδιότητεςunclassified